Clinical characteristics and prognosis of SARS-CoV-2 infection in lung transplant recipients - Zhang, Wenping; Li, Qiangming; Ma, Zeheng; Han, Zhijun; Hu, Shuai; Xia, Tian; Zhu, Zibo; Wei, Li (Frontiers in Surgery, 2024)
Objective This study aimed to investigate the clinical manifestations and prognosis of lung transplant (LTx) recipients infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) during the coronavirus disease (COVID-19) pandemic. Methods The research participants were LTx recipients who underwent surgery and were regularly followed up at our center. From 1 December 2022 to 28 February 2023, during the COVID-19 pandemic in China, research participants were interviewed either online or in person. SARS-CoV-2 nucleic acid or self-tested antigens were detected according to accessibility. Diagnosis and treatment were performed according to the Diagnosis and Treatment Plan for COVID-19 (10th edition) issued by the National Health Commission of the People's Republic of China. Hospitalized patients underwent chest imaging examinations, routine blood tests, biomarkers for infection and inflammation, and biochemical tests, all of which were taken and recorded. Data were analyzed to describe the features of COVID-19 in LTx recipients. Results In total, 52 patients were enrolled in this study, comprising 48 men and 4 women, with a mean age of 51.71 ± 11.67 years. By 1 December 2022, the mean survival period was 33.87 ± 25.97 months, of which 84.61% of the patients (44/52) had a survival period longer than 12 months. The SARS-CoV-2 infection rate in these LTx recipients was 82.69% (43/52), with 3.85% (2/52) of the infected recipients being asymptomatic, 50.00% (26/52) of the infected recipients experiencing mild COVID-19, 11.54% (6/52) having moderate COVID-19, and 17.31% (9/52) having severe or critical COVID-19. The mortality rate among severe and critical patients was 66.67% (6/9). Conclusion LTx recipients in this cohort exhibited a notable susceptibility to SARS-CoV-2, with 82.69% of individuals diagnosed with COVID-19. Moreover, the mortality rate among critically ill patients was high.